2010
DOI: 10.1039/c0cc02683b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle based enhancement of electrochemical DNA hybridization signal using nanoporous electrodes

Abstract: A novel nanoparticle-based enhanced methodology for the detection of ssDNA using nanoporous alumina filter membranes, containing pores of 200 nm in diameter, is reported. The blockage of the pores due to the hybridization is detected by measuring the decrease in the differential pulse voltammetric response of the [Fe(CN)(6)](4-/3-) redox indicator and using screen-printed carbon electrodes as transducing platform. Furthermore, 20 nm gold nanoparticle (AuNPs) tags are used in order to increase the sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 18 publications
(21 reference statements)
1
34
0
Order By: Relevance
“…When the redox molecules was confined the transport direction, especially in biological molecule immobilized channels, it made slower diffusion and reflected to the decrease of DPV signals (line B) around 30 %. This result corresponded to the previous study, reported that immobilized protein [15] or DNA [25] onto the side walls of AAM, exhibiting the signal reduction around 30 -50% upon traced by [Fe(CN)6]4-/3-redox indicator. Then comparing the signals from the location of the redox molecules in �200 nm channel width (line B) to �3.4 nm (line D), it resulted in the signal decreasing from 0.9 to 0.3 uA when transferred in mesoporous silica narorods.…”
Section: Resultssupporting
confidence: 94%
“…When the redox molecules was confined the transport direction, especially in biological molecule immobilized channels, it made slower diffusion and reflected to the decrease of DPV signals (line B) around 30 %. This result corresponded to the previous study, reported that immobilized protein [15] or DNA [25] onto the side walls of AAM, exhibiting the signal reduction around 30 -50% upon traced by [Fe(CN)6]4-/3-redox indicator. Then comparing the signals from the location of the redox molecules in �200 nm channel width (line B) to �3.4 nm (line D), it resulted in the signal decreasing from 0.9 to 0.3 uA when transferred in mesoporous silica narorods.…”
Section: Resultssupporting
confidence: 94%
“…These important advantages of SPEs make them extremely attractive for diverse clinical applications, in both centralized and decentralized settings [45,46]. The use of SPEs for the development of DNA hybridization biosensors has been widely reported [47][48][49][50]. Considerable efforts have been devoted for enhancing the performance, particularly the sensitivity and selectivity of DNA hybridization biosensors based on SPEs.…”
Section: Ternary Monolayers On Disposable (Screenprinted) Gold Electrmentioning
confidence: 99%
“…[121] DPV is used to evaluate antibodies related to the West Nile virus as they are adsorbed in the inner walls of a PAA membrane on a platinum disk electrode. Most remarkable are the works by Merkoçi and coworkers, in which DPV is used in combination of PAA pore blocking to detect different kinds of analytes such as cancer biomarkers [114], DNA hybridization [122], or thrombinthrombin aptamer affinity [123,124]. In a similar approach, Li and co-workers [125] exploit the hindered diffusion of [Fe(CN) 6 ] 3− through PAA pores caused by DNA hybridization into the nanopores to obtain a specific DNA sensor.…”
Section: Biosensingmentioning
confidence: 99%